Kepatuhan Wajib Pajak Memediasi Determinan Penerimaan Pajak Penghasilan - Rachmawati Meita Oktaviani; Pancawati Hardiningsih; Ceacilia Srimindari (Jurnal Akuntansi, 2017)
This study aims to examine and analyze the factors affecting income taxrevenues with tax compliance as an intervening variable. The study consists of threeindependent variables that tax penalties, the service tax authorities, and awareness of thetaxpayer. While this research is tied in income tax revenues and intervening variable is taxcompliance.This study used purpose sampling technique and survey method withquestionnaires in collecting data. Respondent were sampled in this study is an individualtaxpayer who performs is 120 respondent in Semarang. Research data analysis usingmultiple analysis with the path analysis.The results showed that the variable tax penaltiesand service tax authorities an effect on tax compliance, awareness taxpayer has no effecton tax compliance, tax penalties, awareness of taxpayers and taxpayer compliance effecton income tax revenue, the service tax authorities had no effect on tax revenue income.Tax compliance successfully mediate the relationship between the variables ofservice taxauthoritiesagainst income tax revenue. Tax compliancenotsuccessfully mediate therelationship between thetax penalties andawareness taxpayeragainst income tax revenue.